Stabilization of soil hydraulic properties under a long term no-till system - Lozano, Luis Alberto (2014)
The area under the no-tillage system (NT) has been increasing over the last few years. Some authors indicate that stabilization of soil physical properties is reached after some years under NT while other authors debate this. The objective of this study was to determine the effect of the last crop in the rotation sequence (1st year: maize, 2nd year: soybean, 3rd year: wheat/soybean) on soil pore configuration and hydraulic properties in two different soils (site 1: loam, site 2: sandy loam) from the Argentinean Pampas region under long-term NT treatments in order to determine if stabilization of soil physical properties is reached apart from a specific time in the crop sequence. In addition, we compared two procedures for evaluating water-conducting macroporosities, and evaluated the efficiency of the pedotransfer function ROSETTA in estimating the parameters of the van Genuchten-Mualem (VGM) model in these soils. Soil pore configuration and hydraulic properties were not stable and changed according to the crop sequence and the last crop grown in both sites. For both sites, saturated hydraulic conductivity, K0, water-conducting macroporosity, εma, and flow-weighted mean pore radius, R0ma, increased from the 1st to the 2nd year of the crop sequence, and this was attributed to the creation of water-conducting macropores by the maize roots. The VGM model adequately described the water retention curve (WRC) for these soils, but not the hydraulic conductivity (K) vs tension (h) curve. The ROSETTA function failed in the estimation of these parameters. In summary, mean values of K0 ranged from 0.74 to 3.88 cm h-1. In studies on NT effects on soil physical properties, the crop effect must be considered.